Trend 2001 - 2010. Statistics Canada. CANSIM: Labor - Hours of Work and Work Arrangements | Country: Canada | Province: Northwest Territories | Table: Average weekly hours for employees paid by the hour (SEPH), for selected industries classified using the North American Industry Classification System (NAICS) | Variable: Accommodation and food services, Excluding overtime | Units: # Hours, 2001-2010. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-138. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Labor - Hours of Work and Work Arrangements | Country: Canada | Province: Northwest Territories | Table: Average weekly hours for employees paid by the hour (SEPH), for selected industries classified using the North American Industry Classification System (NAICS) | Variable: Accommodation and food services, Excluding overtime | Units: # Hours, 2001-2010. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-138. Dataset: Reports statistics on workers' hours, days worked, job permanency, and work practices in Canada. Examples are usual or actual hours worked, full- and part-time schedules, paid or unpaid overtime, flex-time, shift and on-call work, work from home, seasonal, temporary or permanent jobs, innovative work practices such as teamwork or job rotation, and the availability of personal support or family services such as fitness and recreation services or child care. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Labor and Employment Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Workers, Labor Force, Work Flexibility, Employment, Work Hours